Impact of the interinstitutional cooperation in the fight against theorganized crime (Legal journal - Research in Legal and Social Sciences, 2020)
The  Public  Ministry's  Training  Centre,  in  compliance  with  the  Institutional Strategic Plan, asseses the impact of its training program. In this sense, the Training Centre has reviewed the results of the developed activities in the program named: organized  crime,  class 2019. The objective was  to  strengthen  the  knowledge  and skills of the institutions' servanst who step in the fight against the organized crime. The  institutions  that  took part as  organizers were: CEMP, CIMEE  and ISEPOL, and  the  guest  institutions were: SEPRELAD,  SENAD  and SENABICO. The methodology  was  a  mixed  approach  with  a  correlation level, a  deductive  method was  applied,  the  program's  strenghts  and  weaknesses were  also  analyzed.  The population  consisted of 48 graduates  and  the  sample of 38, which  represents  the 79,2 % of the total. The data collection was made by an online form with 16 items. With  regard  to  the  results, it highlights  the development of critical  thinking,  the formation of sustainable opinions, the ability to harmonize theories in dissent, the enhancement of team work and the importance of the cooperation as an  estrategy to optimize the State's resources, foster transparency, fight againstcorruption and finally  be able to  firmly  get involved in  the  fight  against  this problem.  The  study made possible to obtain information about the students, by assesing the usufulness and relevance of the traineeship in their daily tasks, the incidence of sharing with other team members of the main institutions that work in the area.
Keywords: organized crime; cooperation; training; impact; team work